Islamic business ethics of culinary business actors by Pontianak City - Sari, Sherina Herwidya (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2024)
As a business actor, the importance of behavior in pursuing the world of business, business ethics or moral values is a critical point that becomes an important handle. Business ethics in Islam here has an orientation to maintain the rules that have been applied in accordance with Islamic sharia and do not approach the nature of greed and selfish behavior. Not a few business actors who do not pay more attention to ethics in the scope of their business activities, the role of ethics here is very important, especially in business transactions in it. This study aims to determine the use of business ethics principles in business activities and their implementation in the form of production results by culinary business actors souvenirs of Pontianak City. By using five principles of business ethics in the form of tawhid principles, balance principles, free will principles, responsibility principles, virtue principles, and this research involved 30 business actors who are Muslim and used Likert scale analysis methods. Based on the results of Likert scale analysis, it shows that business actors have used the principles of Islamic business ethics and implemented the form of products that are produced well so that they can be accepted by the market.